2016
DOI: 10.3109/09273948.2016.1142573
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of and Risk Factors for Ocular Hypertension and Secondary Glaucoma in Juvenile Idiopathic Arthritis-associated Uveitis

Abstract: OHT and SG were common in patients with JIA-associated uveitis. Use of immunosuppressive drugs may decrease the risk of developing OHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
1
4
1
1
Order By: Relevance
“…Stroh et al found that children with JIA and raised IOP are threefold more likely to be registered legally blind 13. The mean BCVA was stable at last follow-up at 0.28 logMAR in our population and the overall incidence of blind eyes was 5.3%, in keeping with the rate in recent literature3 but a drastic improvement from an older study,5 where one-third of the uveitic eyes with glaucoma had no perception of light.…”
Section: Discussionsupporting
confidence: 87%
“…Stroh et al found that children with JIA and raised IOP are threefold more likely to be registered legally blind 13. The mean BCVA was stable at last follow-up at 0.28 logMAR in our population and the overall incidence of blind eyes was 5.3%, in keeping with the rate in recent literature3 but a drastic improvement from an older study,5 where one-third of the uveitic eyes with glaucoma had no perception of light.…”
Section: Discussionsupporting
confidence: 87%
“…A study by Skarin et al [28] found that frequencies of cataract and uveitic glaucoma in patients with JIA-U increased with uveitis duration, and cataract was present in 51%, whereas uveitic glaucoma was present in 22% at 24 years, which agrees with our findings (cataract was present in 57.14%, and ocular hypertension and glaucoma were present in 19.05% of our patients with JIA-U). However, a study by Stroh et al [29] reported that the frequency of ocular hypertension or secondary glaucoma in patients with JIA-associated uveitis can be as high as 40%, which is two times as high as our value.…”
Section: Resultscontrasting
confidence: 76%
“…In a recent retrospective analysis including 108 patients with JIA-associated uveitis, the authors described the incidence of ocular hypertension and secondary glaucoma in 40% of eyes at presentation and a three-fold higher incidence of legal blindness during a 5-year median follow-up ( 16 ). Moreover, the authors found a correlation between the use of systemic corticosteroids at presentation and incidence of hypertension/secondary glaucoma, concluding that an early and aggressive immunosuppressive therapy may reduce the risk of developing such complications.…”
Section: Discussionmentioning
confidence: 99%